Between technology and humanity the impact of technology on health care ethics. - Gastmans, Chris; Caritas Catholica Vlaanderen; International conference Caritas Vlaanderen Brussels 18.10.2002 - 19.10.2002 (Leuven Leuven university press, 2002)
In the last decade health care has witnessed a host of technological novelties in the field of diagnostic and therapeutic practices, as well as in the supportive information and communication technology and in various applications of genetics, microbiology and informatics. As a result a few questions need to be answered: -Is health care ethics due dor a splitting up into an ethics of technology (focusing on the ethical implications of new technologies) and an ethics of care (focusing on the ethical problems concerning chronic diseases, decay, disability, end of life)? -How to cope with dependence, limitation, finiteness, suffering, ... in spite of technological progress? -Could a better integration of technology and care preclude situations where patients are being dehumanised? Starting with a philosophical ethical reflection about the possibilities and dangers of technologies in health care, this book highlights both the relation between technology and care, and the normative aspects of economic analyses in health care. Finally, a series of concrete examples from various clinical fields (prenatal diagnosis, genetic tests, digital imaging in psychiatry, tube feeding in care for the elderly, and palliative sedation) will help the authors to consider how to integrate these technologies in a care context aimed upon humaneness. Since each topic is analysed by leading European clinicians and health care ethicists, this book clearly stands for the interdisciplinary approach in health care ethics.
This book may be a rich source of material for reflection on the role, meaning and ends of technology and care, as harmonious aspects of clinical health care practice. However, the authors main concern is to show what such a reflection may consist of and how it can contribute to the inquiry into the experience of technology, the needs of humanity and the development of appropriate health care. This book highlights both the relation between technology and care, and the normative aspects of economic analyses in health care. A series of concrete examples from various clinical fields (prenatal diagnosis, genetic tests, digital imaging in psychiatry, tube feeding in care for the elderly, and palliative sedation) helps the authors to consider how to integrate these technologies in a care context aimed upon humaneness. Each topic is analysed by leading European clinicians and health care ethicists.
V. Tube feeding in elderly care
Keywords: Genetic screening; Medical ethics; Medical technology -- Moral and ethical aspects; Nursing ethics; Bioethical Issues; Bioethics; Biomedical Technology; Ethics, Medical; Health Care Rationing; 174.2 -- Beroepsmoraal van de artsen. Medische beroepsethiek; 241.63*2 -- Theologische ethiek: medische ethiek: dokter; verpleegster; ziekenhuis; 61 -- Geneeskunde. Hygiëne. Farmacie